(2R, 6R)-hydroxynorketamine rapidly potentiates optically-evoked Schaffer collateral synaptic activity. (15th August 2022) - Riggs, Lace M.; Thompson, Scott M.; Gould, Todd D.
Abstract: ( 2R, 6R )-hydroxynorketamine (HNK) is a metabolite of ketamine that exerts rapid and sustained antidepressant-like effects in preclinical studies. We hypothesize that the rapid antidepressant actions of ( 2R, 6R )-HNK involve an acute increase in glutamate release at Schaffer collateral synapses. Here, we used an optogenetic approach to assess whether ( 2R, 6R )-HNK promotes glutamate release at CA1-projecting Schaffer collateral terminals in response to select optical excitation of CA3 afferents. The red-shifted channelrhodopsin, ChrimsonR, was expressed in dorsal CA3 neurons of adult male Sprague Dawley rats. Transverse slices were collected four weeks later to determine ChrimsonR expression and to assess the acute synaptic effects of an antidepressant-relevant concentration of ( 2R, 6R )-HNK (10 μM). ( 2R, 6R )-HNK led to a rapid potentiation of CA1 field excitatory postsynaptic potentials evoked by recurrent optical stimulation of ChrimsonR-expressing CA3 afferents. This potentiation is mediated in part by an increase in glutamate release probability, as ( 2R, 6R )-HNK suppressed paired-pulse facilitation at CA3 projections, an effect that correlated with the magnitude of the ( 2R, 6R )-HNK-induced potentiation of CA1 activity. These results demonstrate that ( 2R, 6R )-HNK increases the probability of glutamate release at CA1-projecting Schaffer collateral afferents, which may be involved in the antidepressant-relevant behavioral adaptations conferred by ( 2R, 6R )-HNK in vivo . The current study also establishes proof-of-principle that genetically-encoded light-sensitive proteins can be used to investigate the synaptic plasticity induced by novel antidepressant compounds in neuronal subcircuits. Highlights: Glutamatergic modulators are under development for the treatment of depression. ( 2R, 6R )-hydroxynorketamine (HNK) exerts rapid antidepressant-like actions. ( 2R, 6R )-HNK potentiates glutamatergic synaptic transmission in the hippocampus. ( 2R, 6R )-HNK promotes glutamate release following optical excitation of CA3 neurons. Optogenetics can reveal drug-induced synaptic plasticity in neuronal subcircuits.